The response of crude palm oil mill to environmental regulation and information-based environmental policies - Jumali, Siti Norliza; Samsi, Aznita; Ahmad, Siti Aznor (2007)
Environmental policies are crucial in ensuring sustainable environmental preservation. But tough environmental regulations mean little if society does not have the resources or will power to back them up. This paper investigates the firms' compliance to environmental regulation and their behavioral response to information-based environmental policies. Three crude palm oil mills in Kedah are surveyed to gather information on the companies’ level of compliance to environmental policies (command and control) and also responsiveness to information-based environmental strategies. Findings found that all three mills not only comply with the environmental regulation, but also applied some of information-based policies listed in Corporate Environmental Reports and Environmental Audit System.